2021
DOI: 10.1161/hypertensionaha.120.16879
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Renin-Angiotensin-Aldosterone System in Young Healthy Black Adults: The African Prospective Study on the Early Detection and Identification of Hypertension and Cardiovascular Disease (African-PREDICT Study)

Abstract: This study presents a detailed profile of the renin-angiotensin-aldosterone system (RAAS), electrolytes, volume loading, blood pressure (BP), and total peripheral resistance in healthy young Black and White adults. We also explored longitudinal associations between BP and RAAS. We included normotensive Black (N=543) and White (N=573) adults (20–30 years) and followed N=324 over ≈4.5 years. We measured clinic (central, brachial) and 24-hour BP, total peripheral resistance and left ventricular dimensions. We det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Our study included apparently healthy black ( n = 587) and white ( n = 585) men and women with a comparable sex distribution and confirmed the influence of ethnicity on s(P)RR levels. As previously reported in this cohort [ 19 ], PRA-s, a measure of renin activity and eq AngII were two-fold higher in white participants as compared to black participants. Prorenin was higher in white participants which is inconsistent with recent relevant studies [ 18 , 41 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our study included apparently healthy black ( n = 587) and white ( n = 585) men and women with a comparable sex distribution and confirmed the influence of ethnicity on s(P)RR levels. As previously reported in this cohort [ 19 ], PRA-s, a measure of renin activity and eq AngII were two-fold higher in white participants as compared to black participants. Prorenin was higher in white participants which is inconsistent with recent relevant studies [ 18 , 41 ].…”
Section: Discussionsupporting
confidence: 85%
“…Independent sample t-tests were used to compare black and white participants. Ethnicity-pooled and ethnicity-specific regression analyses were performed to account for the well-known ethnic heterogeneity in RAS activity [ 19 , 25 ]. Candidate independent variables included age, ethnicity (in ethnicity-pooled analysis), sex, waist circumference, socioeconomic score, 24 h diastolic blood pressure, eGFR, Na + /K + , glucose, LDL-c, CRP, smoking, alcohol use and AEE as independent variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…209 Blacks tend to have a suppressed renin-angiotensin-aldosterone system activity, including low renin status and accordingly, low renin hypertension is common. 210,211 Other hypothesized etiology for more prevalent hypertension among Blacks include sodium abnormalities, epithelial sodium channel changes, altered genes regulating the renin-angiotensin-aldosterone system, increased peripheral vascular resistance, increasing obesity, early vascular aging (large artery stiffness), and underweight phenotype. 120,210 East Asians have a genetically higher salt sensitivity.…”
Section: Pathophysiology Of Raised Bpmentioning
confidence: 99%
“…A large genetic study has shown that renal development is significantly mediated by AD‐associated loci in the AAs, compared to the non‐Hispanic EAs 16 . Furthermore, the renin‐angiotensin‐aldosterone system (RAAS) is markedly less robust in healthy young AA adults than in their EA counterparts 17 . Specifically, AA adults have a greater aldosterone sensitivity than EA adults 18 .…”
Section: Introductionmentioning
confidence: 99%